The impact of fiscal Policy on achieving economic stabilité in Algeria, a standard analytical study - choubar, lyes (Journal of Research in Finance and Accounting, 2026)
During the period 2000-2020, Algeria witnessed the state’s intervention in economic activity through fiscal policy tools represented in public revenues, public expenditures and the public budget with the aim of achieving economic stability. The positive impact on indicators of economic stability, but this impact is weak, which is why the Algerian state must reconsider how to implement financial policy tools.